Variations in practice of thromboprophylaxis across general surgical subspecialties: a multicentre (PROTECTinG) study of elective major surgeries. Issue 12 (30th October 2020) - Liu, David S.; Stevens, Sean; Wong, Enoch; Fong, Jonathan; Mori, Krinal; Fleming, Nicola; Beh, Pith Soh; Crowe, Amy; Howard, Tess; Slevin, Maeve; Jain, Anshini; Gill, Anna Sonia; et al.
Abstract : This multicentre study analysed 6628 elective major procedures across all general surgical specialties. Significant variations in practice of perioperative thromboprophylaxis were identified. These included: (i) use of chemoprophylaxis, (ii) timing of its initiation, (iii) type of anticoagulant administered and (iv) application of extended chemoprophylaxis. These variations were seen within the same procedure, and between different surgeries and subspecialties. The inherent bleeding and venous thromboembolism risks of common procedures are also described. Our findings enable surgeons to compare their practices, and provide baseline data to inform efforts towards optimizing thromboprophylaxis for general surgical patients. Abstract: Background: Despite guidelines recommending perioperative thromboprophylaxis for patients undergoing general surgery, we have observed significant variations in its practice. This may compromise patient safety. Here, we quantify the heterogeneity of perioperative thromboprophylaxis across all major general surgical operations, and place them in relation to their risk of bleeding and venous thromboembolism. Methods: Retrospective review of all elective major general surgeries performed between 1 January 2018 and 30 June 2019 across seven Victorian hospitals was conducted. Results: A total of 5912 patients who underwent 6628 procedures were reviewed. Significant heterogeneity was found in the use of chemoprophylaxis, timing of its initiation, type of anticoagulant administered and application of extended chemoprophylaxis. These variations were observed within the same procedure, and between different surgeries and subspecialties. Contrastingly, there was minimal heterogeneity with the use of mechanical thromboprophylaxis. Oesophago‐gastric, liver and colorectal cancer resections had the highest thromboembolic risk. Breast, oesophago‐gastric, liver, pancreas and colon cancer resections had the highest bleeding risk. Conclusion: Perioperative chemoprophylaxis across general surgery is highly variable. This study has highlighted key areas of variance. Our findings also enable surgeons to compare their practices, and provide baseline data to inform future efforts towards optimizing thromboprophylaxis for general surgical patients.